2011
DOI: 10.1159/000322994
|View full text |Cite
|
Sign up to set email alerts
|

Increased Uric Acid and Glucose Concentrations in Vitreous and Serum of Patients with Diabetic Macular Oedema

Abstract: Background: Diabetic retinopathy (DR) is characterized by blood-retina barrier breakdown induced by local changes in the retina and systemic factors. We investigated vitreous and serum levels of glucose and uric acid (UA) in patients with DR and aimed to describe their correlation with the grade of DR. Methods: Prospective study of 81 patients with DR and 48 non-diabetic controls. Biochemical analysis of vitreous and serum samples was performed. Results: UA and glucose concentrations in vitreous and serum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
3
26
1
Order By: Relevance
“…Furthermore, SUA at baseline is associated with DR and PDR independent of other established risk factors. In support of this, Krizova et al recently demonstrated that increased intra-vitreous levels of UA may be involved in the pathogenesis and progression of DR [35]. Moreover, micro and macrovascular complications cluster; DR is associated with atherosclerosis [36] and cardiorenal complications remain strongly interrelated in diabetes [37], suggesting possible common underlying risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SUA at baseline is associated with DR and PDR independent of other established risk factors. In support of this, Krizova et al recently demonstrated that increased intra-vitreous levels of UA may be involved in the pathogenesis and progression of DR [35]. Moreover, micro and macrovascular complications cluster; DR is associated with atherosclerosis [36] and cardiorenal complications remain strongly interrelated in diabetes [37], suggesting possible common underlying risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-year prospective study in patients with Type 2 DM indicated that SUA concentration was associated with an increase in the severity of DR [23]. SUA may also be involved in the pathogenesis and progression of DR [24]. Researches all above presented the negative influence on eyes.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a more elevated level of SUA in the patients with more severe DR. Krizova et al reported that vitreous concentrations of uric acid were significantly higher in patients with diabetes than in nondiabetic controls [9,10]. An increased concentration in vascular endothelial vascular factor (VEGF) in the vitreous fluid has also been demonstrated in patients with DR [11].…”
Section: Discussionmentioning
confidence: 99%